(3GdHMQ GdRNGQ GdLGeY dePgH YdeGA GdCeUGQ hCUhd abg GdRjOjI GdCWgGQs - (3CMeO Hf jMji Hf GdeQJVj Hf eaVd Hf efUhQ GdMSfj, GdegOj dOjf Gddg,J (B840 (3g` s
(3ChdgG (B:s
(3GdhJQ jVe Edi edcg edckG hbjd ef fGbI TGaY Ci jJHYgG s
(3BNQgG (B:s
(3hGeG ef NGa ebGe QHg hfgG GdfaS Yf Gdghi aEf GdLfI gi GdeChi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B206s
Keywords: (3abg GdePGgH GdCNQis